Development and Validation of Analytical Method for Concurrent Determination of Mupirocin and Beclomethasone Dipropionate in Pharmaceutical Formulation and Perform Forced Degradation Study - Mahavir M. Sharma (Asian Journal of Pharmaceutics (AJP), 2025)
A straightforward, specific, precise, and reproducible technique has been developed and validated for concurrently determining both drugs in their combined dosage form. The analysis employs reverse phase high-performance liquid chromatography with a mobile phase of Methanol: Buffer pH 4 (65:35, v/v) and a Phenomenex Gemini ODS C18 column (200 mm × 4.6 mm, 5.0 μ particle size) as the stationary phase, detecting at a wave length of 215 nm. Linearity was established in the concentration range of 40–120 μg/mL for mupirocin (MUP) and 0.5–1.5 μg/mL for beclomethasone dipropionate (BEC). The %recoveries for both drugs ranged from 99.45% to 99.86% for MUP and 100.10% to 100.39% for BEC. The limits of quantification (LOQ) were determined as 29.11 μg/mL and 0.297 μg/mL at 215 nm for MUP and BEC, respectively. The methods underwent statistical validation for accuracy, precision, specificity, LOQ, and robustness. In addition, a force degradation study following ICH guidelines was conducted, affirming the suitability of the method for analyzing the combined dosage form.